Diffusion-Weighted Magnetic Resonance Imaging in Hepatocellular Carcinoma as a Predictor of a Response to Cisplatin-Based Hepatic Arterial Infusion Chemotherapy - Sung, Pil Soo; Choi, Moon Hyung; Yang, Hyun; Lee, Soon Kyu; Chun, Ho Jong; Jang, Jeong Won; Choi, Jong Young; Yoon, Seung Kew; Choi, Joon-Il; Lee, Young Joon; Bae, Si Hyun (Frontiers in Oncology, 2020)
This study aimed to identify the utility of diffusion-weighted magnetic resonance (MR) imaging with an apparent diffusion coefficient (ADC) map as a predictor of the response of hepatocellular carcinoma (HCC) to cisplatin-based hepatic arterial infusion chemotherapy (HAIC). We retrospectively evaluated 113 consecutive patients with Barcelona Clinical Liver Cancer (BCLC) stage B or C HCC, who underwent gadoxetic acid-enhanced and diffusion-weighted MR imaging. The appropriate cutoff for the pretreatment tumor-to-liver ADC ratio was determined to be 0.741. Of the 113 patients, 50 (44%) presented with a pretreatment tumor-to-liver ADC ratio < 0.741 (low group). Evaluation of the treatment response after 2-3 cycles of HAIC in these 50 patients revealed that 21 patients (42%) experienced an objective response to HAIC. On the other hand, only 11 of the 63 patients (17%) with a pretreatment tumor-to-liver ADC ratio ≥ 0.741 (high group) showed an objective response. Thus, the objective response rate was significantly higher in the low group than in the high group (P = 0.006). Multivariate logistic regression analysis using parameters including perfusion alteration, percentage of non-enhancing portions, and pretreatment tumor-to-liver ADC ratio revealed that a pretreatment tumor-to-liver ADC ratio < 0.741 (odds ratio 3.217; P = 0.014) was the sole predictor of an objective response to HAIC. Overall survival rates were significantly higher in patients with objective responses to HAIC than in those without objective responses (P = 0.001 by log-rank test). In conclusion, patients with BCLC stage C or C HCC with a pretreatment tumor-to-liver ADC ratio < 0.741 showed a favorable intrahepatic response to cisplatin-based HAIC. Therefore, diffusion-weighted MR imaging can play a critical role as a predictor of response to cisplatin-based HAIC in unresectable HCC.